Toxoplasmosis among Random Sample of Blood Donors in Baghdad City - Aboud, Rabia A. (Diyala Journal of Medicine, 2018)
Background: Toxoplasma gondii, Hepatitis B virus and Human immunodeficiency virus infections and blood donors could represent a risk for transmission in blood recipients. Objective: To scarce information about the epidemiology of T. gondii, HBV and HIV infections in blood donors in Iraq. Therefore, prevalence of T. gondii, HBV and HIV infections and associated socio-demographic characteristics at Baghdadis needed. Patients and Methods: The present study were carried out on 142 the blood donors attending National Blood Bank in Baghdad city between October 2013 to October 2014. Volunteers were males, females, different age groups, and different race. Information's about there, previous surgical operations, living with cats at home, samples were taken from different geographical areas in Baghdad. Serological tests were using for investigating of Toxoplasma gondii, Hepatitis B virus and HIV antibodies. Results: The results reported that(78.17%) of the blood donors were in direct contact with stray cats,(29.5%) showed antibodies for Toxoplasma by Latex test, results of the blood samples ELISA -IgM showed that only (1.5%) were positive to Toxoplasma gondii while (28.2%) showed ELISA- IgG positive for Toxoplasma gondii. Conclusion: All tested samples were negative for HIV (0%), only one sample was found to be positive for Hepatitis B virus (0.7%).